Grafting enhances plants drought resistance: Current understanding, mechanisms, and future perspectives - Yang, Le; Xia, Linchao; Zeng, Yi; Han, Qingquan; Zhang, Sheng (Frontiers in Plant Science, 2022)
Drought, one of the most severe and complex abiotic stresses, is increasingly occurring due to global climate change and adversely affects plant growth and yield. Grafting is a proven and effective tool to enhance plant drought resistance ability by regulating their physiological and molecular processes. In this review, we have summarized the current understanding, mechanisms, and perspectives of the drought stress resistance of grafted plants. Plants resist drought through adaptive changes in their root, stem, and leaf morphology and structure, stomatal closure modulation to reduce transpiration, activating osmoregulation, enhancing antioxidant systems, and regulating phytohormones and gene expression changes. Additionally, the mRNAs, miRNAs and peptides crossing the grafted healing sites also confer drought resistance. However, the interaction between phytohormones, establishment of the scion-rootstock communication through genetic materials to enhance drought resistance is becoming a hot research topic. Therefore, our review provides not only physiological evidences for selecting drought-resistant rootstocks or scions, but also a clear understanding of the potential molecular effects to enhance drought resistance using grafted plants.